(untitled) (Gaceta Técnica, 2021)
Cement is one of the most widely used building materials worldwide. For every ton produced, one ton of CO2 is emitted into the atmosphere, additionally, its production requires energy expenditure, implying the environmental effects of the mining activity. An eco-friendly alternative is represented by geopolymeric materials, which are inorganic polymeric matrices that can fulfill the binder function of cement, whose production minimizes the carbon damages. Geopolymers can be made using as precursors industrial residues rich in silicon and aluminum oxides, through an alkaline activation process, representing an alternative for the revaluation of many environmental liabilities, allowing the production of concretes of up to 50 Mpa of compressive strength. In the present investigation, a bibliometric and patentometric analysis of current trends in the use and synthesis of geopolymers was carried out, as well as the evolution of the technological process during the last 20 years. For this, a search equation was developed and later the Patent Inspiration platform was used for patent analysis and Thomson Reuters for scientific publications. It was found that the leading countries in patenting this technology are China, Korea and the United States. The present cartography of geopolymers makes it possible to publicize this technological innovation for the development of environmentally friendly construction materials which have not yet been widely investigated in Venezuela